The Influence of the Magnetic Abrasive Finishing System for Cylindrical Surfaces on the Surface Roughness and MRR - Qate’a, Marwa K.; . kadhum, Ali H; Mustafa, Faiz F. (Al-Khwarizmi Engineering Journal, 2015)
Abstract Magnetic abrasive finishing (MAF) is one of the advanced finishing processes, which produces a high level of surface quality and is primarily controlled by a magnetic field. This paper study the effect of the magnetic abrasive finishing system on the material removal rate (MRR) and surface roughness (Ra) in terms of magnetic abrasive finishing system for eight of input parameters, and three levels according to Taguchi array (L27) and using the regression model to analysis the output (results). These parameters are the (Poles geometry angle, Gap between the two magnetic poles, Grain size powder, Doze of the ferromagnetic abrasive powder, DC current, Workpiece velocity, Magnetic poles velocity, and Finishing time). This work includes the classification of the MAF system, implementation of MAF machine and magnetic poles, preparing ferromagnetic abrasive powder by mix the iron oxide with industrial diamond powder and studying the effects of magnetic abrasive finishing on the MRR and surface roughness. MINITAB software was used to estimate the influence of the Magnetic Abrasive Finishing (MAF) parameters on the MRR and Surface Roughness for a cylindrical duralumin (2024) workpiece. The results show that the poles geometry angle has the biggest influence on MRR (30.18%) followed by Finishing time, Gap, Magnetic poles velocity, Workpiece velocity, Current, Doze, and Grain size powder, respectively. Also the results show that the workpiece velocity has the biggest influence on the surface roughness (23.80%) followed by Doze, Gap, Current, poles geometry angle, Magnetic poles velocity, Grain size powder, and Finishing time, respectively. Regression results show that the decreasing of poles geometry angle from 30°to -30° leads to increasing MRR. While the decreasing of the workpiece velocity from (679 rpm) to (567 rpm) leads to increase the Roughness. Keywords: Magnetic Abrasive Finishing process, Regression model, Material Removal Rate, Surface Roughness.